Politeness Strategies Used by Male and Female Teachers in English Classroom Interaction at SMK Nasional Makassar - Sarmadani, Sarmadani; Wello, Muhammad Basri; Weda, Sukardi (Har Press Indonesia, 2023)
This research aimed to finding out (1) What are courteousness methodologies utilized by male in classroom interaction at SMK Nasional Makassar, (2) What are courteousness methodologies utilized by female instructors in classroom interaction at SMK Nasional Makassar, (3) What are the most dominant politeness techniques utilized by male and female instructors in classroom interaction at SMK Nasional Makassar. There are 4 English teachers including 2 male teachers and 2 female teachers at SMK Nasional who participated. This study using a qualitative descriptive method. Data research was collected through observation. Based on the results researcher found that politeness strategies used by male were thirty-four utterances used by male teachers from the total utterances were eighty-eight. The researcher found twenty-one utterances as bold on record, seven utterances as positive politeness, five utterances as off-record and one utterance as Say-Nothing. Moreover, politeness strategies utilized by teachers based on the results found that there were fifty-four utterances used by female teachers from the total utterances were eighty-eight. In addition, there were thirty-three utterances as bold on record. Five utterances as off-record. Seven utterances as positive politeness. Nine utterances as Say-Nothing strategy. The most dominant courteousness techniques utilized by male and female teachers in English classroom at SMK Nasional Makassar was bold on-record. It can conclude that the teachers have close relationship with his students.